2011
DOI: 10.1007/s10803-011-1315-9
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Autism Phenotype Questionnaire: Mothers Versus Fathers of Children with an Autism Spectrum Disorder

Abstract: Parents of individuals with autism were examined using the Broad Autism Phenotype Questionnaire (BAPQ; Hurley et al. in J Autism Dev Disord 37:1679-1690, 2007) assessing BAP-related personality and language characteristics. The BAPQ was administered to parents as a self-report and as an informant (spouse)-based measure. Results indicated the same pattern of differences for the informant and best-estimate (average between self-report and informant scores) reports. Fathers were rated as more "aloof" than mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
(80 reference statements)
6
31
3
1
Order By: Relevance
“…These frequencies are generally consistent with other studies showing that 9% to 21% of mothers and 9% to 40% of fathers meet criteria for BAP [2,8,17]. However, our pattern of results contrasts with a recent larger study to determine BAP occurrence in ASD families and the general population [3].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These frequencies are generally consistent with other studies showing that 9% to 21% of mothers and 9% to 40% of fathers meet criteria for BAP [2,8,17]. However, our pattern of results contrasts with a recent larger study to determine BAP occurrence in ASD families and the general population [3].…”
Section: Discussionsupporting
confidence: 89%
“…revealed that individuals with BAP traits in the social domain measured by the BAPQ display certain social cognitive deficits (for example, facial identity recognition, facial expression recognition and theory of mind) as well as general impairment in social skills as rated during actual social interactions [6]. Gender differences in the number and distribution of BAP traits (males > females) have also been reported using interview and questionnaire assessments of BAP [7,8]. Specifically, in ASD families, the aloof phenotype occurs more frequently in fathers, whereas mothers demonstrate more rigidity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These personality traits may also be related to performance on cognitive BAP measures (see Losh et al 2009) as well as the core behavioural domains of autism. A recent study by Seidman et al (2011) reported sex differences in personality traits in fathers and mothers of children with autism. Using the Broad Autism Phenotype Questionnaire, fathers were rated by their respective partners as more 'aloof' than mothers, whilst mothers were rated by their respective partners as more 'rigid' than fathers.…”
Section: Personality Traitsmentioning
confidence: 99%